Foraging Ecology and Contaminant Burdens of Ringed Seals (Pusa hispida) in the Central Canadian Arctic - Ross, Tyler Robert (2020)
Increasing temperatures have led to declines in the extent of Arctic sea ice. Due to their reliance on sea ice and central position within Arctic marine food webs, ringed seals (Pusa hispida) are particularly vulnerable to these climate-mediated changes. I sought to investigate factors affecting ringed seal foraging and contaminant burdens in the central Canadian Arctic. Specifically, I used three dietary estimation techniques to examine how seal diets differed in accordance with demographic and environmental variables. Contaminant concentrations in seal tissues were also assessed in relation to trophic position and climate indices. Diet analyses revealed intraspecific and temporal variation in ringed seal foraging. Changes in sea ice phenology also influenced ratios of stable isotopes. Contaminant concentrations exhibited similar demographic variation and differed in accordance with several environmental variables. Ongoing monitoring of ringed seals is important, as climate-mediated shifts in prey composition and contaminants may be indicators of broader ecological changes.